Assessing Psychological Fitness to Drive for Intoxicated Drivers: Relationships of Cognitive Abilities, Fluid Intelligence, and Personality Traits - Nechtelberger, Martin; Vlasak, Thomas; Senft, Birgit; Nechtelberger, Andrea; Barth, Alfred (Frontiers in Psychology, 2020)
Our study explores the relationships between psychological and driving-related personality traits, fluid intelligence and cognitive abilities for drivers whose driving licence has been revoked due to intoxicated driving (alcohol and/or drugs). We were able to show that highly significant impacts on cognitive functions derive from the participants’ age and fluid intelligence. In addition, driving-related personality traits such as emotional instability, a sense of responsibility and self-control contributed significantly to some of the cognitive abilities that are important for fitness to drive. Additionally, the mediating effects of fluid intelligence in the model are discussed. Traffic psychologists can use this knowledge in their assessment of drivers, mainly regarding the possible compensation of cognitive deficits regarding the fitness to drive.